2021
DOI: 10.1002/pssr.202000479
|View full text |Cite
|
Sign up to set email alerts
|

A High‐Performance and Long‐Term Air‐Stable CH3NH3PbI3/C8BTBT Heterojunction Photodetector Fabricated via Chemical Vapor Deposition

Abstract: Organic–inorganic hybrid perovskites are considered as a class of star materials for optoelectronic devices. However, the stability is one of the big issues. Herein, an MAPbI3 perovskite film with high stability is fabricated using chemical vapor deposition (CVD). The stability and performance of the MAPbI3 photodetector are further improved by constructing an MAPbI3 heterojunction with the organic semiconductor C8BTBT. The MAPbI3/C8BTBT heterojunction photodetector shows a wide spectral response range from ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…The device performance parameters were obviously improved, including detectivity, response time, and responsivity. [ 171 ] Different from layer‐by‐layer planar heterojunction structure, bulk heterojunction is also widely researched. [ 172 ] Xia et al adapted CH 3 NH 3 PbI 3 /C8‐BTBT bulk heterojunction in photodetector, as shown in Figure 11f.…”
Section: Strategies For Performance Improvement Of Btbt Derivatives‐b...mentioning
confidence: 99%
“…The device performance parameters were obviously improved, including detectivity, response time, and responsivity. [ 171 ] Different from layer‐by‐layer planar heterojunction structure, bulk heterojunction is also widely researched. [ 172 ] Xia et al adapted CH 3 NH 3 PbI 3 /C8‐BTBT bulk heterojunction in photodetector, as shown in Figure 11f.…”
Section: Strategies For Performance Improvement Of Btbt Derivatives‐b...mentioning
confidence: 99%
“…[35] The relatively wide band gap (≈3.8 eV) of C8-BTBT offers the ability to demonstrate good UV-responsive characteristics and potential applications with persistent photoconductivity. [36][37][38] The molecular structure of C8-BTBT is displayed in Figure S4a (Supporting Information). Spin-coating was adopted to fabricate the C8-BTBT film top-wrapped onto the InGaAs NW arrays to construct the artificial photosynaptic device.…”
Section: Resultsmentioning
confidence: 99%
“…The organic polymer layer could act as an effective charge carrier extraction layer to enhance carrier transport, due to its inherent high mobility and energy level matching, and as a waterproof layer to prevent perovskite film degradation. [36][37][38] On the other hand, Sun et al proposed to embed gold nanoparticles into perovskite thin films to achieve higher responsivity as well as a faster light response speed. [39] Lee et al reported the introduction of gold nanostars into perovskites to develop PDs with hot electron transfer and efficient light-harvesting properties, which greatly improved the device performance.…”
Section: Introductionmentioning
confidence: 99%
“…The organic polymer layer could act as an effective charge carrier extraction layer to enhance carrier transport, due to its inherent high mobility and energy level matching, and as a waterproof layer to prevent perovskite film degradation. [ 36–38 ] On the other hand, Sun et al. proposed to embed gold nanoparticles into perovskite thin films to achieve higher responsivity as well as a faster light response speed.…”
Section: Introductionmentioning
confidence: 99%